(untitled) (Journal of Bangladesh Academy of Sciences, 2013)
Present study attempted to detect the biochemical and serological markers other than HBsAg of Hepatitis B virus (HBV) infection in perspective of Bangladesh. Out of 100 HBsAg positive patients (79 male and 21 female), 23 were found to be HBeAg positive, and 59 were anti-HBe positive. Nineteen (24.05%) and 43 (54.43%) male patients were found to be HBeAg and anti-HBe positive, respectively; while 4 (19.04%) and 16 (76.19%) females were HBeAg and anti-HBe positive, respectively. Three males (3.79%) had abnormal serum bilirubin, 21 (26.58%) had abnormal ALT and 9 (11.39%) had abnormal AST levels; whereas, among the female patients, 1 (4.76%) had abnormal serum bilirubin, 2 (9.52%) had abnormal ALT and 1 (4.76%) had abnormal AST levels. Taken together, present findings suggest that HBeAg can be used as an alternate marker for detecting the active viral replication in HBV carriers with raised serum ALT levels. DOI: http://dx.doi.org/10.3329/jbas.v37i1.15680 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 1, 51-56, 2013